1975
DOI: 10.1007/bf01906387
|View full text |Cite
|
Sign up to set email alerts
|

Collateral vessel formation: isolation of a transferable factor promoting a vascular response

Abstract: Collateral vessel formation to the kidney was induced by renal artery stenosis or embolization in six dogs. Extracts from control and collateral-forming kidneys were assessed for their ability to promote a vascular response in the hamster cheekpouch. The highly significant response evoked by particulate and soluble fractions of cytoplasm from collateral-forming kidneys suggests a humoral element in collateral vessel formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1977
1977
1992
1992

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…It also confirmed a significant increase in endothelial cell labeling of renal veins and epithelium of the ureter draining the kidney, previously demonstrated in this laboratory (Cowan et al, 1978). This observation provides further support for the presence of a humoral substance participating in vascular neogenesis (Cuttino et al, 1975;Schaper et al, 1971). …”
supporting
confidence: 87%
See 1 more Smart Citation
“…It also confirmed a significant increase in endothelial cell labeling of renal veins and epithelium of the ureter draining the kidney, previously demonstrated in this laboratory (Cowan et al, 1978). This observation provides further support for the presence of a humoral substance participating in vascular neogenesis (Cuttino et al, 1975;Schaper et al, 1971). …”
supporting
confidence: 87%
“…Earlier attempts to demonstrate growth-promoting factors in the drainage from ischemia tissues generally were performed late following arterial stenosis, in the 2nd to 4th week (Cuttino et al, 1975), primarly because the experimental protocol demanded arteriographic documentation of collateral formation. This study has confirmed that these vessels are generally difficult to visualize by angiography or gross inspection early in the course, when the mitogenic activity is at its height.…”
Section: Discussionmentioning
confidence: 99%
“…Quite recently, a humoral factor that promotes growth of capillaries has been isolated from tumors 33 and from ischemic kidneys. 34 Perhaps in pathological hypertrophy there is insufficient production, excessive destruction, or inability to respond to a similar humoral stimulus. If so, therapy designed to shorten diffusion distance may become possible.…”
Section: -1mentioning
confidence: 99%
“…An unanticipated observation suggested that under some conditions this underlying premise might not hold. We employed the hamster cheek pouch to assay a vasoproliferative factor that may contribute to collateral arterial development (6). While using this assay system to characterize several candidates as mediator of the vascular response we found that one of them, the platelet-derived growth factor (PDGF), induced a vascular response that displayed a highly alinear dose-response relationship.…”
Section: Introductionmentioning
confidence: 99%